Human papillomavirus infection in the oral cavity of HIV patients is not reduced by initiating antiretroviral therapy. (19th June 2016) - Shiboski, Caroline H.; Lee, Anthony; Chen, Huichao; Webster-Cyriaque, Jennifer; Seaman, Todd; Landovitz, Raphael J.; John, Malcolm; Reilly, Nancy; Naini, Linda; Palefsky, Joel; Jacobson, Mark A.
Abstract : Objective: The incidence of human papillomavirus (HPV)-related oral malignancies is increasing among HIV-infected populations, and the prevalence of oral warts has reportedly increased among HIV patients receiving antiretroviral therapy (ART). We explored whether ART initiation among treatment-naive HIV-positive adults is followed by a change in oral HPV infection or the occurrence of oral warts. Design: Prospective, observational study. Methods: HIV-1 infected, ART-naive adults initiating ART in a clinical trial were enrolled. End points included detection of HPV DNA in throat-washes, changes in CD4 + T-cell count and HIV RNA, and oral wart diagnosis. Results: Among 388 participants, 18% had at least one HPV genotype present before initiating ART, and 24% had at least one genotype present after 12–24 weeks of ART. Among those with undetectable oral HPV DNA before ART, median change in CD4 + count from study entry to 4 weeks after ART initiation was larger for those with detectable HPV DNA during follow-up than those without ( P = 0.003). Both prevalence and incidence of oral warts were low (3% of participants having oral warts at study entry; 2.5% acquiring oral warts during 48 weeks of follow-up). Conclusion: These results suggest: effective immune control of HPV in the oral cavity of HIV-infected patients is not reconstituted by 24 weeks of ART; whereas ART initiation was not followed by an increase in oral warts, we observed an increase in oral HPV DNA detection after 12–24 weeks. The prevalence of HPV-associated oral malignancies may continue to increase in the modern ART era.